ANALISIS PENGHEMATAN BIAYA LISTRIK DI KANTOR DINAS KETENAGAKERJAAN DAN ESDM PROVINSI BALI PASCA TERPASANG PLTS ATAP 40 KWP - Adi Febriana Putra, I Kadek; Dwi Giriantari, Ida Ayu; Sukerayasa, I Wayan (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUM, 2022)
PLN's electricity sales in 2020 reached 234.5 TWh, while electricity consumption in Bali Province throughout 2020 was 4.9 TWh. In this study, PLTS roof supporting parking at the Office of the Manpower and ESDM Office of the Province of Bali is used as a location for installing PLTS in the use of new and renewable energy which has an impact on saving electricity bills and reducing CO? emissions. PLTS is installed with a total capacity of 40 kWp with an on grid configuration. Based on the research results, the simulation uses HelioScope software using two scenarios. In scenario 1 with an optimal inclination angle of 14.79°, the potential for energy production is 59.251,00 kWh/year, while in scenario 2 with an optimal tilt angle of 6.35°, the potential for energy production is 59.251,00 kWh/year. PLTS production from June to December 2021 is 35,287.90 kWh with savings on electricity bill costs of Rp. 67,640,740.00 and is able to reduce total CO? gas emissions by 27,233.33 kg CO?.